Current practices and perceived influences of diet diaries usage in pediatric dental practice - Chaitali Hambire; Umesh Vishnu Hambire (Wolters Kluwer Medknow Publications, 2022)
Introduction: The diet diaries act as an important tool for the assessment of diet. There is a paucity of studies to assess the usage of diet diaries for the management of caries in high-risk patients by pediatric dentists. The study was conducted to explore the perceptions of the pediatric dentists regarding the possible difficulties and their solutions for the usage of diet diaries in their dental office. Materials and Methods: A questionnaire was designed incorporating a diet dairy to understand its perception and utilization by the pediatric dentists while preparing the diet modifications for their patients. A qualitative research methodology was used to understand the factors associated with adherence of the pediatric patients to the issued diet dairies. Observations: Majority of pediatric dentists (78%) collected the information regarding the diet verbally without using diet diaries. Most common reason was constraints were monetary (43%) followed by time (35%). Other reasons were poor compliance of parents and pediatric patients (12%). About 10% of pediatric dentists perceived that they lacked the skills needed for appropriate dietary counselling. The results of the qualitative study showed that adhering to diet diaries was a multi-contextual phenomenon. Conclusions: In order to use the diet diary as an efficient dietary assessment and monitoring tool multifaceted interventions are needed. A supportive healthcare system, motivation of parents as well as child along with an efficient tool seems to be a need for the success of the utilization of diet diaries.